The Problem of the Essence of Matriarchy from the Point of View of the Evolution of Human Intellect and Consciousness: Feminism and Promising Tools for the Formation of a Cognitive Society - Suleimenov, Ibragim; Vitulyova, Yelizaveta; Matrassulova, Dinara (Journal of Ecohumanism, 2024)
It is shown that the issue of the formation of cognitive society in modern conditions is closely related to the problems of feminism. This conclusion is based on the fact that human intellect and consciousness had and have a dual nature - they simultaneously contain both individual and collective components. The collective component is predominantly connected with the feminine basis, and the individual component with the masculine one. In the period of matriarchy, the collective component of human consciousness was dominant, which determined the subordination of ancient communities to suprapersonal information objects perceived as the "will of the gods", etc. Women - priestesses, etc. - were a kind of "avatars" of suprapersonal information objects. Nowadays, the importance of the collective component of consciousness is increasing due to the development of telecommunication technologies, and interaction with suprapersonal information objects is of pronounceable importance. The collective component of human consciousness is closely connected with the feminine basis, consequently such practices as “women's circles” and their analogs are of importance too. Such practices are the "germs" of the transition to a cognitive society that uses the resources of the suprapersonal level of information processing.